Efficient Multi-Material Structured Thin Film Transfer to Elastomers for Stretchable Electronic Devices - Xiuping Ding; Jose M. Moran-Mirabal (Micromachines, 2022)
Stretchable electronic devices must conform to curved surfaces and display highly reproducible and predictable performance over a range of mechanical deformations. Mechanical resilience in stretchable devices arises from the inherent robustness and stretchability of each component, as well as from good adhesive contact between functional and structural components. In this work, we combine bench-top thin film structuring with solvent assisted lift-off transfer to produce flexible and stretchable multi-material thin film devices. Patterned wrinkled thin films made of gold (Au), silicon dioxide (SiO2), or indium tin oxide (ITO) were produced through thermal shrinking of pre-stressed polystyrene (PS) substrates. The wrinkled films were then transferred from the PS to poly(dimethylsiloxane) (PDMS) substrates through covalent bonding and solvent-assisted dissolution of the PS. Using this approach, different materials and hybrid structures could be lifted off simultaneously from the PS, simplifying the fabrication of multi-material stretchable thin film devices. As proof-of-concept, we used this structuring and transfer method to fabricate flexible and stretchable thin film heaters. Their characterization at a variety of applied voltages and under cyclic tensile strain showed highly reproducible heating performance. We anticipate this fabrication method can aid in the development of flexible and stretchable electronic devices.